Prognostic utility of hybrid coronary computed tomography angiography and myocardial perfusion imaging in elderly patients with suspected coronary artery disease - Nammas, Wail; Ajosenpää, Iina; Maaniitty, Teemu; Stenström, Iida; Bax, Jeroen J.; Knuuti, Juhani; Saraste, Antti (Elsevier BV, 2025)
Background: The prognostic utility of sequential hybrid imaging strategy (coronary computed tomography angiography (CCTA) followed by positron emission tomography (PET) myocardial perfusion imaging in those with obstruction) in the elderly remains unclear. We explored the predictors of adverse outcome in patients ≥65, versus those <65 years, who underwent hybrid CCTA-PET for evaluation of coronary artery disease (CAD).
Methods: Retrospectively, we evaluated 1948 patients (43.8% ≥65 years) referred for CCTA due to suspected CAD from 2008 through 2016. Patients with obstructive CAD by CCTA (n = 657) underwent 15O-water PET under adenosine stress.
Results: Mean age was 61.9±9.9 years, 58.9 % were females. Elderly patients had more often obstructive CAD by CCTA, and ischemia by PET. During a median follow-up of 6.7 years, the composite adverse outcome (all-cause death, myocardial infarction, or unstable angina) occurred more often in patients ≥65, versus those <65 years (14.2 % vs. 5.6 %, p < 0.001). Ischemic CAD assessed by hybrid imaging predicted events with a hazard ratio of 5.65 (95 % CI 2.35-13.57) in older patients, and 7.01 (95 % CI 3.08-15.94) in younger patients, compared with patients without CAD. The c-statistic of a multivariable model including the hybrid CCTA-PET finding (adjusted for clinical risk predictors) for predicting the composite outcome was similar between patients ≥65, versus those <65 years (p = 0.1). There was no interaction between age category and the hybrid CCTA-PET finding for prediction of events (p = 0.9).
Conclusion: The prognostic utility of hybrid CCTA-PET for predicting adverse events at long-term follow-up was similar between patients ≥65 and those <65 years.